Coandǎ Effect - Punte, Harmen; Overmars, Machiel (TMAL02 Expert Conference, 2020)
The Coandǎ effect is a phenomenon used in several applications such as health care, robotics and aeronautics. However, this effect is often interpreted incorrectly. The aim of this paper is to explain the Coandǎ effect and elaborate on the working principle behind it. In section 3 the common definition is given and additions are made to replenish it. It is explained when the Coandǎ effect is applicable for airfoils and finally some applications in modernday aeronautics are presented, for example V/STOL, ACHEON and NOTAR.